2003
DOI: 10.1037/0097-7403.29.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Modularity as a fish (Xenotoca eiseni) views it: Conjoining geometric and nongeometric information for spatial reorientation.

Abstract: When disoriented in a closed rectangular tank, fish (Xenotoca eiseni) reoriented in accord with the large-scale shape of the environment, but they were also able to conjoin geometric information with nongeometric properties such as the color of a wall or the features provided by panels located at the corners of the tank. Fish encoded geometric information even when featural information sufficed to solve the spatial task. When tested after transformations that altered the original arrangement of the panels, fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
119
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 163 publications
(131 citation statements)
references
References 37 publications
12
119
0
Order By: Relevance
“…the colour of a wall) in order to reorient themselves [e.g. Wsh: redtail splitWns (Xenotoca eiseni): Sovrano et al 2002Sovrano et al , 2003goldWsh (Carassius auratus) : Vargas et al 2004; birds: chicks (Gallus gallus): Vallortigara et al 1990Vallortigara et al , 2004pigeons (Columba livia) : Kelly et al 1998;Vargas et al 2004a;mammals: rhesus monkeys: Gouteux et al 2001;tamarins: Deipolyi et al 2001]. Interestingly, however, a "primacy" of geometric information seems to be apparent in spatial reorientation.…”
Section: Introductionmentioning
confidence: 99%
“…the colour of a wall) in order to reorient themselves [e.g. Wsh: redtail splitWns (Xenotoca eiseni): Sovrano et al 2002Sovrano et al , 2003goldWsh (Carassius auratus) : Vargas et al 2004; birds: chicks (Gallus gallus): Vallortigara et al 1990Vallortigara et al , 2004pigeons (Columba livia) : Kelly et al 1998;Vargas et al 2004a;mammals: rhesus monkeys: Gouteux et al 2001;tamarins: Deipolyi et al 2001]. Interestingly, however, a "primacy" of geometric information seems to be apparent in spatial reorientation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a substantial corpus of 'geometry' studies tested various vertebrate species, including fish [9,10], birds [11,12] and monkeys [13] (see review in Ref. [14]).…”
Section: Modularity Of Geometry In Doubtmentioning
confidence: 99%
“…According to Gallistel (Gallistel, 1990), geometry would be encoded in allocentric coordinates, thus providing a metric frame to the 'cognitive map' (Tolman, 1948; O'Keefe and Nadel, 1978; Morris et al, 1982;Wang and Spelke, 2002). Subsequent work has shown that fish [Xenotoca eiseni (Sovrano et al, 2002;Sovrano et al, 2003); Carassius auratus (Vargas et al, 2004)], birds [domestic chicks (Vallortigara et al, 1990); pigeons (Kelly et al, 1998)], rodents [rats (Golob and Taube, 2002)], nonhuman primates [rhesus monkey , tamarins (Deipolyi et al, 2001)] and humans (Hermer and Spelke, 1994;Hermer and Spelke, 1996) reoriented according to the geometric information (i.e. metric and the left-right discrimination sense) specified by the macroscopic layout of surfaces (reviewed by Wang and Spelke, 2002;Cheng and Newcombe, 2005;Vallortigara, 2009).…”
Section: Introductionmentioning
confidence: 99%